Implikasi Keputusan Majelis Utama Desa Pakraman Bali Nomor 01/KEP/PSM-3/MDP BALI/X/2010 tentang Kedudukan Wanita Bali dalam Keluarga dan Pewarisan - Warsana, I Made (Universitas Negeri Malang, 2021)
The purpose of this study was to analyze the philosophical basis and implications of the Decision of the Main Assembly of Bali Pakraman Village Number 01/Kep/Psm-3/MDP Bali/X/2010 on the position of Balinese women in the family and inheritance. This study used a normative juridical method with a philosophical and conceptual approach, which discussed legal rules or regulations as a system associated with legal events. The study results showed that the philosophical basis for the Decision of the Main Assembly of the Bali Pakraman Village Number 01/Kep/Psm-3/MDP Bali/X/2010 was a patrilineal system Balinese society which did not provide opportunities for Balinese women to become heirs. The implication of the decision of the Main Assembly of the Bali Pakraman Village Number 01/Kep/Psm-3/MDP Bali/X/2010 was the realization of gender equality between Balinese men and women in obtaining rights, although with different amounts of inheritance.